The structural evolution of high-density polyethylene during crazing in liquid medium. (May 2015) - Yarysheva, Alena Yu.; Rukhlya, Ekaterina G.; Yarysheva, Larisa M.; Bagrov, Dmitry V.; Volynskii, Aleksandr L.; Bakeev, Nikolai F.
Graphical abstract: Highlights: The structure of HDPE during crazing in liquid medium was visualized. The lamellae serve as walls of the craze. The separation of lamellae makes the main contribution to the deformation. The crazing model of HDPE is constructed based on the AFM images. Abstract: Atomic force microscopy (AFM) was employed to study structural transformations occurring in high-density polyethylene (HDPE) during deformation in a liquid medium by crazing mechanism. Processing of the obtained images yielded the parameters of HDPE structure at different tensile strains. It was shown that crazing causes the development of a fibrillar–porous structure in the interlamellar space, the fragmentation of lamellae, and the displacement of lamella fragments relative to each other. Moreover, the deformation is accompanied by the separation of lamellae and the long period increases in the proportion to the tensile strain. The scheme of HDPE deformation upon crazing in liquid medium was constructed based on the AFM images.